A video‐ and feedback‐based approach to teaching communication skills in undergraduate clinical dental education: The student perspective. (25th March 2021) - Krause, Felix; Ziebolz, Dirk; Rockenbauch, Katrin; Haak, Rainer; Schmalz, Gerhard
Abstract: Objective: Student evaluation of a communication‐education programme that combined patient consultation videos with peer‐ or expert‐based feedback. Methods: A self‐perception questionnaire was given to undergraduate dental students who had undertaken a curricular communication training and feedback programme, in which each participant was videoed three times during a patient interview or consultation, subsequently receiving either peer (PG) or expert feedback (EG). The questionnaire used feedback programme content to evaluate student perspectives, ascertaining whether the students experienced a gain in knowledge and professional conversational skills, whether videos or feedback helped them improve more and general questions about the structure and content of the curriculum. Differences between feedback groups were analysed (Mann‐Whitney U test). Results: 45 participants (peer group: n = 23, expert group: n = 22) took part in the study. The peer group experienced watching their video (38%) and receiving feedback (33%) as their major beneficial aspect to improve communication skills (watching fellow student´s video: 17%, providing feedback: 12%). The expert group experienced the major effect in receiving expert feedback (73%, video watching: 27%). The students said that communication skills should be a core competency in dental education learning outcomes (PG: 4.48 ± 0.67, EG: 4.41 ± 0.67; P > 0.05) and that communication curricula should include video‐based feedback (PG: 3.91 ± 0.73, EG: 4.00 ± 0.93; P > 0.05). Conclusion: Watching videos and both receiving and providing peer group feedback were experienced as helpful in improving students' communication skills. These findings suggest that a longitudinal communication curriculum, which includes both video‐based peer feedback and correlated self‐reflection, is a promising learning approach for dental education.